The practical past - White, Hayden V. 1928-2018 (FlashPoints, 2014)
Intro -- Contents -- Preface -- 1. The Practical Past -- 2. Truth and Circumstance: What (if Anything) Can Properly Be Said about the Holocaust? -- 3. The Historical Event -- 4. Contextualism and Historical Understanding -- 5. Historical Discourse and Literary Theory -- Afterword -- Notes -- Index